2008
DOI: 10.2323/jgam.54.259
|View full text |Cite
|
Sign up to set email alerts
|

Candida kanchanaburiensis sp. nov., a new ascomycetous yeast species related to Pichia nakazawae isolated in Thailand

Abstract: Three yeast strains, ST-633, ST-634 and ST-635, isolated from the fruit body of a mushroom, Coprinus sp., and rotted fruit of guava collected in the western region of Thailand, were found to represent a hitherto undescribed species. This yeast is related to Pichia nakazawae var. akitaensis, P. nakazawae var. nakazawae and Pichia philogaea in the D1/D2 domain of 26S rDNA but 12 (2.3%), 13 (2.5%) and 15 (2.8%) nucleotides are different from these taxa, respectively, suggesting the distinctness of the Thai strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 40 publications
(26 reference statements)
0
13
0
Order By: Relevance
“…The three nucleotide differences found in the D1/D2 region in contrast to the 46 differences in the ITS region between CBS 8583 T and C. naeodendra can be seen as a good example why the D1/D2 region, a region that is still commonly used as an exclusive marker in studies for the identification and delimitation of species belonging to commonly known yeast genera (Nakase et al 2008, 2010a, b, Ganter et al 2010, de Garcia et al 2010, Mestre et al 2010), alone is often not sufficient for species delimitation in yeasts; especially within the Yamadazyma clade. Several other yeast taxonomic studies have also proven this to be true in species from other genera such as Blastobotrys (Kurtzman 2007), Debaryomyces (Groenewald et al 2008), Saturnispora (Canelhas et al 2010) and Rhodotorula (Libkind et al 2010), and shown that sequences of additional regions are necessary in order to separate the closely related species from one another.…”
Section: Discussionmentioning
confidence: 99%
“…The three nucleotide differences found in the D1/D2 region in contrast to the 46 differences in the ITS region between CBS 8583 T and C. naeodendra can be seen as a good example why the D1/D2 region, a region that is still commonly used as an exclusive marker in studies for the identification and delimitation of species belonging to commonly known yeast genera (Nakase et al 2008, 2010a, b, Ganter et al 2010, de Garcia et al 2010, Mestre et al 2010), alone is often not sufficient for species delimitation in yeasts; especially within the Yamadazyma clade. Several other yeast taxonomic studies have also proven this to be true in species from other genera such as Blastobotrys (Kurtzman 2007), Debaryomyces (Groenewald et al 2008), Saturnispora (Canelhas et al 2010) and Rhodotorula (Libkind et al 2010), and shown that sequences of additional regions are necessary in order to separate the closely related species from one another.…”
Section: Discussionmentioning
confidence: 99%
“…In the latest edition of The Yeasts, a Taxonomic Study, six ascosporogenous species (Yamadazyma philogaea, Y. akitaensis, Y. mexicana, Y. nakazawae, Y. scolyti, Y. triangularis) and 23 asexual species assigned to the genus Candida were placed in the Yamadazyma clade . Since then, additional species of the genus Candida in this clade have been found Nakase et al, 2008;AmIn et al, 2011;Buddie et al, 2011;Burgaud et al, 2011;Groenewald et al, 2011) and many novel species of the genus Yamadazyma have been discovered and described such as Yamadazyma terventina, Y. siamensis, Y. phyllophila, Y. paraphyllophila, Y. ubonensis, Y. insecticola, Y. epiphylla, Y. riverae, Y. dushanensis and Y. kitorensis (Ciafardini et al, 2013;Kaewwichian et al, 2013b;Junyapate et al, 2014;Jindamorakot et al, 2015;Lopes et al, 2015;Wang et al, 2015;Nagatsuka et al, 2016). In addition, three known species of the genus Candida were transferred to the genus Yamadazyma as novel combinations, namely Yamadazyma olivae, Y. tumulicola and Y. takamatsuzukensis (Nagatsuka et al, 2016).…”
mentioning
confidence: 99%
“…Members of the Yamadazyma clade exhibit an association with the gut of beetles and other insects, flowers, tree exudates, plants, mushroom, deep-sea coral, water samples, and marine and mangrove habitats (Nakase et al , 2008; Burgaud et al , 2011; Groenewald et al , 2011; Kurtzman, 2011; Lachance et al , 2011; Kaewwichian et al , 2013; Junyapate et al ., 2014). According to these reports, 20 species in the Yamadazyma clade have been isolated from the gut or frass of insects and 10 species have been obtained from plants.…”
Section: Novel Species Delineation and Phylogenetic Placementmentioning
confidence: 99%
“…In Kurtzman (2011), Yamadazyma philogaea , the type species of the genus, as well as Y. akitaensis , Y. mexicana , Y. nakazawae , Y. scolyti , Y. triangularis and 28 Candida species are placed in the Yamadazyma clade. Since then, many novel species of the genus Candida in this clade have been described, for example Candida kanchanaburiensis , C. khao-thaluensis , C. vaughaniae , C. tallmaniae , C. oceani , C. sirachaensis , C. sakaeoensis , C. phyllophilla and C. vitiphila (Nakase et al , 2008; Burgaud et al , 2011; Groenewald et al , 2011; Limtong et al ., 2012; Limtong & Kaewwichian, 2013). Recently, five species of the genus Yamadazyma , namely Y. terventina , Y. siamensis , Y. phyllophila , Y. paraphyllophila and Y. ubonensis , were proposed from strains isolated in Italy, Taiwan and Thailand (Ciafardini et al ., 2013; Kaewwichian et al , 2013; Junyapate et al ., 2014).…”
mentioning
confidence: 99%